2021
DOI: 10.46881/ajh.v6i0.234
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Savings and Investment Patterns Among Rural Farming Households in Yewa Division, Ogun State, Nigeria

Abstract: This study examined the analysis of savings and investment patterns among rural farming households in Yewa Division of Ogun State, Nigeria. The study was based on primary data obtained in a cross-section of 120 farming households drawn by multi- stage random sampling.Results showed that 44.2% were males with age bracket 31 – 40 years. The famers were mostly married 90.8% and 52.5% practice Islamic religion. The percentage of those that were educated was 64.2% and majority of these farmers (37.5%) had a farming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…And this might be attributed to the consciousness on production activities that they had with experience on farm management, since almost all the populace in that area were agrarians and had better educational background than those in Gombe Central. This is in line with Akerele and Oyebanjo (2014) who reported that education is an important factor that makes an individual to have a sense of recognition and utilization of investment opportunities. It is also in line with Kolo et al (2015) who had the view that years of experience have a positive effect of an individuals' managerial ability, decisions, perception and understanding of socioeconomic factors affecting farm activities.…”
Section: Results and Discussion Activity Based Classification (Abc) M...supporting
confidence: 90%
“…And this might be attributed to the consciousness on production activities that they had with experience on farm management, since almost all the populace in that area were agrarians and had better educational background than those in Gombe Central. This is in line with Akerele and Oyebanjo (2014) who reported that education is an important factor that makes an individual to have a sense of recognition and utilization of investment opportunities. It is also in line with Kolo et al (2015) who had the view that years of experience have a positive effect of an individuals' managerial ability, decisions, perception and understanding of socioeconomic factors affecting farm activities.…”
Section: Results and Discussion Activity Based Classification (Abc) M...supporting
confidence: 90%
“…Literature review showed that the existing literature poorly addressed this thematic in banana and plantain production and in Benin ( Abiola et al, 2020 ; Akerele et al, 2019 ; Blazy et al, 2009 ; Chabi et al, 2018 ; Dé et al, 2019 ; Faï et al, 2018 ; Patel et al, 2020 ). As matter of fact, previous studies used the statistical approach ( Ahouangninou et al, 2021 ; Bellamy, 2013 ; Loyola et al, 2018 ), while analyzing in a general way the limiting factors in banana and plantain production ( Akinyemi et al, 2013 ; Baruwa et al, 2015 ; Dassou et al, 2021 ; Muthee et al, 2019 ; Nandwani, 2010 ).…”
Section: Introductionmentioning
confidence: 99%